Political Participation of Santri in the 2017 Regional Elections in Nagan Raya Regency - Aklima Aklima; Ramzi Murziqin; Reni Shintasari; Aja Sanawiyah (UIN Sunan Gunung Djati, 2021)
This research deals with the participation of students in Islamic boarding schools (dayah), which tend to deepen religion so that political information is limited. This study aims to determine the political participation of students in Nagan Raya Aceh 2017. This research is important because it looks at the attitude of students in political power relations. The urgency of this research is to understand the political culture of the santri, which is not only seen from the Kyai as a determinant of political choices. This research uses a qualitative method of the case study approach. The results of this study indicate that the behavior of voters (santri) with the Michigan School approach where the political attitudes and choices are chosen is not only based on the leadership of the pesantren / santri but there is direct involvement by the participation of the students with three aspects.